Digital realization method of FFT and its application in adjusting velocity damping coefficient of inertial navigation system - Wang Yujie; Zhang Yang; Ma Xintai; Gao Minghao; Zheng Zhipeng (MATEC Web of Conferences, 2022)
Aiming at the velocity damping feedback system commonly used in inertial navigation, this paper proposes the principle of decomposing the output attitude of inertial system based on FFT algorithm and gives the principle of spectrum adjustment ratio. The effectiveness of the algorithm is verified from two aspects: data simulation and actual system solution. In addition, in the design and implementation of FFT algorithm, the butterfly computation of operator symmetry is applied to effectively reduce the complexity of the algorithm, and the dual core chip technology is applied to reduce the impact of the complex algorithm on the system timing. The engineering applicability of the algorithm is demonstrated.